2015
DOI: 10.5152/eurjrheumatol.2015.0093
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-lymphocyte ratio in children with familial Mediterranean fever: original article

Abstract: Objective: The aim of present study was (a) to evaluate the relationship between the neutrophil/lymphocyte (N/L) ratio and mutation types of familial Mediterranean fever (FMF) in children and (b) to evaluate the relationship between the N/L ratio and age.Material and Methods: Three hundred forty-three children with familial Mediterranean fever in the attack-free period and 283 healthy control children were included in the study. Patients were divided into subgroups according to mutation types. Neutrophil and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Since NLR reflects both immune pathways and is probably less affected by confounding conditions, it may be more informative than other widely used markers, such as IL‐6, tumor necrosis factor‐α, or CRP . Specifically, the NLR has been found to be elevated in specific inflammatory‐related conditions, such as acute bacterial meningitis, Crohn's disease, allergic rhinitis, familial Mediterranean fever, and obesity in children …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Since NLR reflects both immune pathways and is probably less affected by confounding conditions, it may be more informative than other widely used markers, such as IL‐6, tumor necrosis factor‐α, or CRP . Specifically, the NLR has been found to be elevated in specific inflammatory‐related conditions, such as acute bacterial meningitis, Crohn's disease, allergic rhinitis, familial Mediterranean fever, and obesity in children …”
mentioning
confidence: 99%
“…17 Specifically, the NLR has been found to be elevated in specific inflammatory-related conditions, such as acute bacterial meningitis, Crohn's disease, allergic rhinitis, familial Mediterranean fever, and obesity in children. 15,[18][19][20][21] The growing interest in the role of inflammation in psychiatric disorders and the availability of blood counts in clinical populations have resulted in a few studies that have shown increased NLR in psychiatric patients, mostly in patients with affective symptoms, but also in those with schizophrenia. 12,[22][23][24][25] Platelets are involved in the secretion of proinflammatory as well as anti-inflammatory processes, and leukocytes and progenitor cells accumulate in areas of inflammation.…”
mentioning
confidence: 99%
“…This occurs because delayed apoptosis and growth hormones are stimulated by stem cells resulting in an increase in neutrophils and accelerated apoptosis accompanied by redistribution of lymphocytes so that neutrophils increase. [7,[9][10] Retrospective studies in Spain obtained NLR results >7 and eosinopenia as markers of mortality in bacteremia and prospective studies in the Czech Republic obtained NLR >6.2 as a diagnostic bacteremia. While in this study the cut-off of NLR ≥1.3.…”
Section: Results This Research Was Conducted At H Adam Malik Generalmentioning
confidence: 99%
“…[8] Increased neutrophils occur during systemic inammation caused by delayed apoptosis and stem cell stimulation by growth hormone and decreased lymphocytes due to redistribution of lymphocytes to the lymphatic system accompanied by accelerated apoptosis. [7,[9][10] Research that assesses NLR begins in adults but still few in children where several studies report that an increase in NLR is associated with poor prognosis and ideal cut-off still varies with grades 3 to 5.4. Therefore, research is needed to assess NLR in children because NLR is easy, simple with a relatively low cost so that it can be used in daily practice.…”
Section: Introductionmentioning
confidence: 99%
“…It is a new biomarker of inflammation and can be used as an indicator and prognostic marker of inflammation. The neutrophilto-lymphocyte ratio (NLR) is a useful marker that predicts disease progression and mortality in inflammatory disease [5][6][7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%